Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content 1. Realizing an innovative design vision for clothes suitable for girls with visual impairments Dr. Roua Suhail Qadi 2. Information sources for the virtual audience about the Uyghur crisis and its impact on public opinion regarding China’s policy are analyzed through An analytical study of the Arabic China News page on Twitter Dr. Hussein Abdalla Saad 3. Studying some variables related to social capital of rural people in some villages of Kafr El-Sheikh Governorate – Egypt Dr. Walaa Abdelatif Shabaan , Dr. Dalia Hassan Hebish, Dr. Amany Said Elkholy 4. Social Responsibility and The Development of The Human Element: A Descriptive Study on A Sample of Beneficiaries of Social Responsibility Programs at The Royal Commission in Yanbu Mr. Suhayb Mousa Abu Shurayyan 5. The social and economic cost of divorce from the perspectives of employees at social development committees in Riyadh City Mr. Mamdouh Abdalla Elheky 6. Analysis of the tools and materials used in tailoring, embroidering and weaving the Bisht, the stages of embroidering the Bisht, its names and colours Co-Prof. Khyrah Awad Awadh Alzahrani 7. Factors leading to the quality of family life and their relationship to resilience in the Corona crisis in Jeddah Governorate Mrs. Hana Ali Aali Al-Malki 8. Self-Efficacy Beliefs of Yemeni Graduate Students about themselves as Competent Researchers Prof. Mohammad Abdu Ahmed Al-Mekhlafi , Dr. Osamah Mohammed Abdu Al-Mekhlafi